Differences in injury risk and characteristics of injuries between novice and experienced runners over a 4-year period - Kemler, E.; Blokland, D.; Backx, F.; Huisstede, B. (The Physician and Sportsmedicine, 2018)
Objectives: Running is increasingly popular, but also carries a high injury risk, especially in novice runners. This study investigates differences in incidence and characteristics of running-related injuries (RRIs) between novice and experienced runners in the open population, in order to adapt to more specific needs for future prevention programs.